The Effect of Demographic Character on the Intention of Muslim Consumer Behavior to Shop at Neighbor Store - Wandhansari Sekar Jatiningrum; Amalia Yuli Astuti (Jurnal Teknik Industri, 2019)
This study aims to find out factors related to the behavioral intention of Muslim consumers to shop in neighborhood stores. The Islamic leaders urged the Muslim community to do the social movement to buy for neighborhoods. Its movement is as one form of spirit 212. Spirit of the actions of Muslims in Indonesia in December 2016 through prayer and prayer together to strengthen the kinship of Muslims. The behavioral intention of Muslim consumers to shop at a neighborhood store in Yogyakarta is thought to be influenced by attitude, subjective norms, behavioral control, religiousness, and affective commitment to be affiliated with spirit. Consumers have the characteristics of adhering to Islamic principles. Demographic characters are also considered to influence consumer preferences for each factor. In the descriptive analysis, the average respondent's answer to religious factors has the highest score than other factors.  In the independent t-tests and ANOVA, the average responses of answers on gender significantly different on education, age, occupation, and income.